On the Etymology of the Armenian Verb տանիմ - SIMONYAN, NEKTAR (Bulletin of Yerevan University B: Philology, 2021)
The article dwells upon different versions of the verb տանիմ whose origin has always been considered unclear. The study results substantiate G. Jahukyan’s assumption on the Indo-European origin of this verb. Besides, the study reveals that the genuine etyma of the verb տանիմ are also the semes “1.win, conquer; 2.percolate” which have not been noted by anyone earlier.